“BAKAS LEWU”: POLITICAL BROKER IN THE MANDUING TAHETA VILLAGE ELECTION, CENTRAL KALIMANTAN - Anyualatha Haridison (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
Bakas Lewu is a group of elders in the Dayak Ngaju language of Central Kalimantan. Previous studies have been more oriented towards mapping brokers in mobilizing material resources to influence voters. The purpose of this article is to explore the role of Bakas Lewu as political brokers, especially how they work, involving culture and social power, which has been discussed to a limited extent. This study was conducted qualitatively and the main data source came from interviews with key informants who knew about the village head election (Pilkades) cases in Manduing Taheta, then analyzed in depth and interactively. This study shows that Bakas Lewu as political brokers play an important role in mobilizing political support based on social relations, kinship, and local Dayak culture by relying on interpersonal communication, narrative control, and social networks to build community trust and loyalty. This phenomenon emphasizes that political power in the village is more influenced by personal and social relationships than material transactions. This study challenges the dominant approach that sees political brokers in Indonesia as transactional actors, by highlighting the importance of local social and cultural dynamics. These findings indicate the diversity of political brokerage practices and suggest more research on how social relations, such as kinship and loyalty, play a role in mobilizing political support, opening up new perspectives in the study of local politics in Indonesia.